Proportion and efficiency of different serve techniques in relation to winning in elite female volleyball - Häyrinen, M.; Inkinen, V.; Mikkola, T.; Linnamo, V. (World Congress of Performance Analysis of Sport IX, 2012)
Serve is an important skill in volleyball in relation to winning matches especially in men`s top-level volleyball. The goals of serving are either to score a direct point or to reduce the attack options of the opponent. The purpose of this study was to analyse the serve techniques and the serve efficiency in relation to winning a rally at two levels in elite female volleyball. The serves were analyzed from World Championships 2010 (WC) and Junior European Championships 2010 (JEC). The number of analyzed serves was 656 for WC and 678 for JEC. The final result of each rally was also recorded. Serve techniques were divided into three categories: jump serves (JS), jump float serves (JF) and float serves (FL). The efficiency of a serve (SE) was analyzed using a 5-point scale (5=ace, 4=reception goes over the net/the receiving team has no chance to attack, 3=opponent has limited attack options, 2=opponent has all attack options and 1=serve error). Chi-Square -test was used for statistical analysis. The use of different serve techniques differed significantly (p<.001) between the two levels. JF was used most in both levels (WC 71 %, JEC 89 %) and JS least used (WC 10 %, JEC 4 %). The efficiency of the JFs was higher in JEC (p<.01). In WC JS and in JEC JF was the most efficient technique (WC p<.01, JEC p<.001). (Table 1.) On average 42 % of the rallies were won with own serve. No significant differences were found in winning a rally on different serve techniques either between the two levels or in either levels. Significant differences (p<.001) in winning a rally were found between serve efficiencies in each serve technique in both levels. (Table 2.) The proportion of jump float serves has increased considerably and the proportion of aces and errors was quite similar compared to the previous studies. (Palao et al. 2009; Quiroga et al. 2010.) To conclude there were no differences between serve techniques in relation to winning rallies. The winning percentage of a rally was higher with higher serve efficiency